Gut Microbiota: The Potential Key Target of TCM’s Therapeutic Effect of Treating Different Diseases Using the Same Method—UC and T2DM as Examples - Zhang, Boxun; Liu, Ke; Yang, Haoyu; Jin, Zishan; Ding, Qiyou; Zhao, Linhua (Frontiers in Cellular and Infection Microbiology, 2022)
Traditional Chinese herbal medicine often exerts the therapeutic effect of “treating different diseases with the same method” in clinical practice; in other words, it is a kind of herbal medicine that can often treat two or even multiple diseases; however, the biological mechanism underlying its multi-path and multi-target pharmacological effects remains unclear. Growing evidence has demonstrated that gut microbiota dysbiosis plays a vital role in the occurrence and development of several diseases, and that the root cause of herbal medicine plays a therapeutic role in different diseases, a phenomenon potentially related to the improvement of the gut microbiota. We used local intestinal diseases, such as ulcerative colitis, and systemic diseases, such as type 2 diabetes, as examples; comprehensively searched databases, such as PubMed, Web of Science, and China National Knowledge Infrastructure; and summarized the related studies. The results indicate that multiple individual Chinese herbal medicines, such as Rhizoma coptidis (Huang Lian), Curcuma longa L (Jiang Huang), and Radix Scutellariae (Huang Qin), and Chinese medicinal compounds, such as Gegen Qinlian Decoction, Banxia Xiexin Decoction, and Shenling Baizhu Powder, potentially treat these two diseases by enriching the diversity of the gut microbiota, increasing beneficial bacteria and butyrate-producing bacteria, reducing pathogenic bacteria, improving the intestinal mucosal barrier, and inhibiting intestinal and systemic inflammation. In conclusion, this study found that a variety of traditional Chinese herbal medicines can simultaneously treat ulcerative colitis and type 2 diabetes, and the gut microbiota may be a significant target for herbal medicine as it exerts its therapeutic effect of “treating different diseases with the same method.”